2009
DOI: 10.1007/s00572-009-0234-5
|View full text |Cite
|
Sign up to set email alerts
|

Fern-associated arbuscular mycorrhizal fungi are represented by multiple Glomus spp.: do environmental factors influence partner identity?

Abstract: Symbioses involving arbuscular mycorrhizal fungi (AMF) are among the most important ecological associations for many plant species. The diversity of AMF associated with ferns, however, remains poorly studied. Using recently designed Glomus-specific primers, we surveyed the AMF community associated with ferns from deciduous, broad-leaved second-growth forest habitats at the eastern edge of the piedmont region of central Virginia, USA. Results indicate that this molecular approach may be a useful tool for detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 57 publications
1
17
0
2
Order By: Relevance
“…Pteridophyte sporophytes are well known to associate with a wide range of AM fungi (Zhang et al 2004;West et al 2009), whereas mycoheterotrophic gametophytes, such as Botrychium (Winther and Friedman 2007) and Psilotum (Winther and Friedman 2009), exhibit very specific associations with particular members of the Glomeraceae. In the present study, the most frequently observed (≥20 total instances) VTs were VT 80,166,191, and 219 of the Glomeraceae.…”
Section: Discussionmentioning
confidence: 99%
“…Pteridophyte sporophytes are well known to associate with a wide range of AM fungi (Zhang et al 2004;West et al 2009), whereas mycoheterotrophic gametophytes, such as Botrychium (Winther and Friedman 2007) and Psilotum (Winther and Friedman 2009), exhibit very specific associations with particular members of the Glomeraceae. In the present study, the most frequently observed (≥20 total instances) VTs were VT 80,166,191, and 219 of the Glomeraceae.…”
Section: Discussionmentioning
confidence: 99%
“…Las micorrizas y las bacterias fijadoras de N 2 atmosférico, conocidos como biofertilizantes, inciden favorablemente en el desarrollo de las plantas (West et al, 2009). El humus de lombriz, la gallinaza y el residuo del hongo de champiñón aportan materia orgánica (Eghball et al, 2002).…”
Section: Introductionunclassified
“…Los hongos micorrízicos arbusculares (HMA) actúan como aceleradores del crecimiento al aumentar la absorción del fósforo y ayudan en la protección contra patógenos (Alarcón y Ferrera, 1999Mena et al, 2006;West et al, 2009;Smith y Smith, 2011;Singh et al, 2013); también pueden influir en el proceso estructural y de agregación del suelo (Rilling y Mummey, 2006). Dentro de los HMA se encuentra Glomus con 85 especies, pero la más importante en la agricultura es G. fasciculatum, estudiada en frutales, forestales, hortalizas y leguminosas.…”
Section: Introductionunclassified
See 2 more Smart Citations